LIFE TABLES OF Mononychellus progresivus DORESTE AND Tetranychus urticae (KOCH) (ACARINA: TETRANYCHIDAE) IN YUCCA - MESA-C., NORA CRISTINA; BELLOTTI, ANTHONNY; DUQUE, MYRIAM CRISTINA (Revista Colombiana de Entomología, 1987)
Tetranychid mites are considered important pests of casava, Manihot esculenta Crantz in different regions of the world, especially during the dry season. M. progresivus Doreste prefers the genus Manihot as a food source while T. urticae (Koch) is a generalist that attacks a number of crops. The objective of this study was to know some aspects of the biology of the two species such as the developmental time, minimum developmental threshold, and physiological time. Experiments were carried out in environmentally controlled chambers at 15, 20, 25 and 30°C and 75 ± 50/o R.H. For adult females, longevity, and reproductive periods duration, as well as reproductive capacity, was studied at 20, 25 and 30°C. Egg-to-adult developmenta! time was 41.4, 19.05, 10.26, and 7.82 days for M. progresivus and 29.7, 15.9, 9.05, and 6.56 days for T. urticae at 15, 20, 25 and 30°C respectively. For total development, M. progresivus required 140 degreedays while T. urticae required 123.6 degree-days. A survivorship curve was constructed for all stages and lifetable statistics as a net reproductive rate (R0), generation time, and intrinsic rate of natural increase were estimated.